Зохиогч нь тодорхойгүй “Дөрвөн ойрдын түүх тууж” зохиолын судлалын асуудал - Сүхбаатар, Надмид (Historia Mongolarum, 2003)
It appears, the anonymous historical source entitled “Dörben oyirad-un teüke tughuji”, was created by a lama in Durbet aimag of Khovd’s periphery-province, in 1770. It is a valuable and prerequisite historical source for Four Oirats’ history, notably, for Zuungar’s and Durbet history.